Analysing thermal comfort perception of students through the class hour, during heating season, in a university classroom. (15th November 2017) - Mishra, A.K.; Derks, M.T.H.; Kooi, L.; Loomans, M.G.L.C.; Kort, H.S.M.
Abstract: Indoor to outdoor transitions, and the subsequent occupant adaptation, impact thermal perception of occupants and their evaluation of a building. A mixed methods thermal comfort study in a classroom of Eindhoven University of Technology was conducted to provide a better understanding of thermal perception of students as they move into and adapt to their classroom environment. Data was collected over two weeks during heating period, with different heating set-points. A total of 384 students, in seven undergraduate level lectures, participated voluntarily. The thermal sensation vote, obtained at different time points through classes — 10 min, 20 min, and 45 min — was found to be significantly different (p < 0.05). In the start of a lecture, perception varies primarily depending on the outside temperature, operative temperature, gender, and where the occupant came from. Comparing the two weeks' observations, second week having a 1.5 °C lower set-point, revealed that the most considerable differences occurred in the immediate response phase after indoor–outdoor transition. For nearly 20 min post transition, participants retain a thermal memory of their last exposure, gradually adapting as the lecture proceeds. Graphical abstract: Highlights: Thermal comfort study conducted in classroom, 384 student participants. Thermal sensation votes changed significantly through class hour. Where students were coming from to the class impacted post-transition perception. Adaptation to new environment near complete in ∼20 min post-transition.